Late-Stage Functionalization of Guanine-Based Nucleosides, Nucleotides, and Oligonucleotide: Synthesis and Derivatization of Tricyclic Nucleoside Analogues - Ma, Ao-Di; Chen, Wei-Jia; Sun, Wen-Wu; Wu, Bin (Organic letters, 2024)
We report here the synthesis of tricyclic nucleoside analogues via acid-catalyzed cyclization of guanine with 1,1,3,3-tetramethoxypropane. The method enables the use of hydroxyl-unprotected antiviral drugs (acyclovir, ganciclovir, and penciclovir), guanosines, oligonucleotide, and triazole-linked nucleoside dimers as substrates. Nucleoside trimer and tetramer were synthesized by derivatization reactions.